2009
DOI: 10.4049/jimmunol.0902854
|View full text |Cite
|
Sign up to set email alerts
|

Mycolactone Suppresses T Cell Responsiveness by Altering Both Early Signaling and Posttranslational Events

Abstract: Mycolactone is a diffusible lipid toxin produced by Mycobacterium ulcerans, the causative agent of a necrotizing skin disease referred to as Buruli ulcer. Intriguingly, patients with progressive lesions display a systemic suppression of Th1 responses that resolves on surgical excision of infected tissues. In this study, we examined the effects of mycolactone on the functional biology of T cells and identified two mechanisms by which mycolactone suppresses cell responsiveness to antigenic stimulation. At noncyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
97
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(105 citation statements)
references
References 36 publications
(45 reference statements)
7
97
1
Order By: Relevance
“…Since mycolactone displays cytopathic effects in vitro (10), we assessed T-cell viability in mycolactoneinjected mice. Confirming our previous studies showing that primary T cells are relatively resistant to mycolactone cytotoxicity (6), no evidence of enhanced apoptosis could be demonstrated by flow-cytometric analysis of T cells in peripheral blood, PLNs and spleen, or by staining of LN sections (Fig. S1).…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…Since mycolactone displays cytopathic effects in vitro (10), we assessed T-cell viability in mycolactoneinjected mice. Confirming our previous studies showing that primary T cells are relatively resistant to mycolactone cytotoxicity (6), no evidence of enhanced apoptosis could be demonstrated by flow-cytometric analysis of T cells in peripheral blood, PLNs and spleen, or by staining of LN sections (Fig. S1).…”
Section: Resultssupporting
confidence: 66%
“…Mycolactone was known to block the capacity of primary T cells to produce multiple cytokines upon activation (2,6). Here, we show that mycolactone also impairs their migratory properties.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In addition, several in vitro studies have suggested that mycolactone could inhibit cytokine and chemokine production from immune cells such as T cells, macrophages, and dendritic cells [9][10][11][12][13]. These observations clearly suggested that mycolactone presents immunosuppressive effects and may have an important role in the successful infection of M. ulcerans in humans.…”
Section: Discussionmentioning
confidence: 90%
“…Injection of mycolactone into guinea pig produced an ulcer similar to Buruli ulcer [4]. Mycolactone inhibits the production of various cytokines, chemokines, and other secreted immune modulators [7] from immune cells such as monocytes [8], macrophages [9], dendritic cells [10], and T cells [11][12][13]. When a mycolactone-deficient strain of M. ulcerans was injected into model animals, a granuloma was successfully developed and the bacteria were cleared from the infected regions [14,15], suggesting that mycolactone has a suppressive effect on cell-mediated immune responses.…”
Section: Introductionmentioning
confidence: 99%